Redox‐Addressable Single‐Molecule Junctions Incorporating a Persistent Organic Radical. Issue 23 (5th April 2022) - Naghibi, Saman; Sangtarash, Sara; Kumar, Varshini J.; Wu, Jian‐Zhong; Judd, Martyna M.; Qiao, Xiaohang; Gorenskaia, Elena; Higgins, Simon J.; Cox, Nicholas; Nichols, Richard J.; Sadeghi, Hatef; Low, Paul J.; et al.
Abstract: Integrating radical (open‐shell) species into non‐cryogenic nanodevices is key to unlocking the potential of molecular electronics. While many efforts have been devoted to this issue, in the absence of a chemical/electrochemical potential the open‐shell character is generally lost in contact with the metallic electrodes. Herein, single‐molecule devices incorporating a 6‐oxo‐verdazyl persistent radical have been fabricated using break‐junction techniques. The open‐shell character is retained at room temperature, and electrochemical gating permits in situ reduction to a closed‐shell anionic state in a single‐molecule transistor configuration. Furthermore, electronically driven rectification arises from bias‐dependent alignment of the open‐shell resonances. The integration of radical character, transistor‐like switching, and rectification in a single molecular component paves the way to further studies of the electronic, magnetic, and thermoelectric properties of open‐shell species. Abstract : A verdazyl radical, stable in its open‐shell state at ambient conditions, has been used to fabricate single‐molecule devices that show enhanced charge‐transport efficiency, electrochemical transistor behaviour, and rectification. All the properties arise from the presence of an unpaired electron, strongly localised on the verdazyl core.